Prognostic factors and treatment of pediatric acute lymphoblastic leukemia - Jae Wook Lee; Bin Cho (2017)
The event-free survival (EFS) for pediatric acute lymphoblastic leukemia (ALL) has shown remarkable improvement in the past several decades. In Korea also, a recent study showed 10-year EFS of 78.5%. Much of the improved outcome for pediatric ALL stems from the accurate identification of prognostic factors, the designation of risk group based on these factors, and treatment of appropriate duration and intensity according to risk group, done within the setting of cooperative clinical trials. The schema of first-line therapy for ALL remains mostly unchanged, although many groups have now reported on the elimination of cranial irradiation in all patients with low rates of central nervous system relapse. Specific high risk subgroups, such as Philadelphia chromosome-positive (Ph+) ALL and infant ALL continue to have significantly lower survival than other ALL patients. The introduction of tyrosine kinase inhibitors into therapy has led to enhanced outcome for Ph+ ALL patients. Infant ALL patients, particularly those with MLL rearrangements, continue to have poor outcome, despite treatment intensification including allogeneic hematopoietic cell transplantation. Relapsed ALL is a leading cause of mortality in pediatric cancer. Recent advances in immunotherapy targeting the CD19 of the ALL blast have shown remarkable efficacy in some of these relapsed and refractory patients. With improved survival, much of the current focus is on decreasing the long-term toxicities of treatment. Key words: Acute lymphoblastic leukemia, Child, Prognostic factors, Treatment, Long-term effects